Acute toxicity, oxidative stress and DNA damage of chlorpyrifos to earthworms (Eisenia fetida): The difference between artificial and natural soils. (September 2020) - Zhu, Lei; Li, Bing; Wu, Ruolin; Li, Wenxiu; Wang, Jun; Wang, Jinhua; Du, Zhongkun; Juhasz, Albert; Zhu, Lusheng
Abstract: Pesticides can damage the soil environment, including damage to sentinel organisms such as earthworms. When assessing the toxicity of pesticides towards earthworms, assays are usually performed using standardized artificial soil, however, soil physicochemical properties may affect pesticide toxicity. In the present study, the toxicity of a commonly used insecticide (chlorpyrifos) to earthworms ( Eisenia fetida ) was determined in artificial soil and three typical natural soils (fluvo-aquic soil, black soil and red clay) by measuring acute and subchronic toxicity. Soil tests were conducted to measure the acute toxicity of chlorpyrifos to Eisenia fetida quantified by the half lethal concentration (LC50 ) while subchronic toxicity tests assessed the impact of low dose chlorpyrifos exposure (0.01, 0.1, 1 mg/kg; up to 56 d) on reactive oxygen species content, antioxidant enzymes activities, detoxifying enzyme activity, malondialdehyde content, and 8-hydroxydeoxyguanosine content. Subchronic toxicity was quantified using the integrated biomarker response (IBR) which highlighted that the toxicity of chlorpyrifos in artificial and natural soils was not the same. Outcomes from artificial soil studies may underestimate (fluvo-aquic soil and red clay) or overestimate (black soil) chlorpyrifos effects. Graphical abstract: Image 1 Highlights: Chlorpyrifos caused oxidative and DNA damage to earthworms. Chlorpyrifos subchronic toxicity to earthworms in soils was compared using IBR. Chlorpyrifos had significant toxicity difference between artificial and natural soil.